When the State is Absent: A Study of LGBT Community in Jakarta - Gadis Arivia; Abby Gina Boangmanalu (Yayasan Jurnal Perempuan, 2015)
This study provides an overview of problems faced by LGBT in Indonesia. There are four issues raised i.e. the meaning of gender and sexual orientation, violence and abuse, the role of the state , and the meaning of happiness. This study uses a sample of 60 respondents living in big cities, especially in Jakarta. However, the strength of this study lies not in the result of the survey, but the result of the indepth interviews. From this study it was found that in the context of a conservative state, the respondents are more open through interviews. This study unearth LGBT’s meaning of life under the repressive and absence role of the state.